A double-edged sword: High interest rates in capital control regimes - Gudmundur S. Gudmundsson; Gylfi Zoega (Kiel Institute for the World Economy (IfW), 2016)
This paper describes the relationship between central bank interest rates and exchange rates under a capital control regime. Higher interest rates may strengthen the currency by inducing owners of local currency assets not to sell local currency off shore. There is also an effect that goes in the opposite direction: higher interest rates may also increase the flow of interest income to foreigners through the current account, making the exchange rate fall. The historical financial crisis now under way in Iceland provides excellent testing grounds for the analysis. Overall, the experience does not suggest that cutting interest rates moderately from a very high level is likely to make a currency depreciate in a capital control regime, but it highlights the importance of effective enforcement of the controls.
Keywords: G01; E42; E52; E58; 330; financial crises; capital controls; policy rates; exchange rates